Impaired HLA capping capacity of peripheral blood lymphocytes in Duchenne muscular dystrophy. Issue 3 (June 1984) - Sensi, A; Venturoli, A; Traniello, S; Lucci, M; Vullo, C; Conighi, C; Mattiuz, P L; Båricordi, O R
Abstract : The cap capacity in nine Duchenne muscular dystrophy (DMD) patients and in 23 healthy male subjects (14 adults and nine neonates) has been investigated by inducing capping of HLA molecules. The evaluation of capping percentages ranged in healthy controls from 44 to 61 with a mean value of 53.39 +/- 4.89, while DMD patients displayed cap capacity of percentages varying from 15 to 38 with a mean value of 31.5 +/- 7.42. Statistical significance of the differences between the two groups, assessed by the Mann-Whitney U test, was p less than 0.00003. A correlation was found in DMD patients between cap capacity and age (tau = +0.657, p = 0.012). The results confirm previous reports of Ig capping impairment noted in B cells of the whole lymphocyte population, supporting the hypothesis of a systemic cellular defect in DMD patients. The data obtained suggest that HLA capping could overcome some of the technical difficulties of Ig capping and could be used as a diagnostic aid in antenatal detection of DMD.